Model for Increasing SMEs' Cultural Competitiveness through Authenticity, Brand Image, and Human Capital with Adaptive Capacity as a Moderator - Muhammad Yasir Arafat Pohan; Acai Sudirman; Iskandar Muda (Komunitas Dosen Indonesia, 2025)
The main objective of this study is to analyse the influence of authenticity, brand image, and human capital on the competitiveness of cultural SMEs, with adaptive capacity as a moderating variable. A quantitative approach model was employed, utilizing 200 samples of cultural SMEs in North Sumatra, selected through a purposive sampling method. The data obtained were analyzed using the SEM-PLS method, which includes both the outer model and the inner model. According to the data analysis, the results obtained confirmed that authenticity, brand image, and adaptive capacity have a positive and significant impact on the competitiveness of cultural SMEs. The results of other studies have found that human capital does not have a significant effect on the competitiveness of cultural SMEs. Then, for moderation analysis, it was found that adaptive capacity only strengthens the relationship between brand image and cultural SMEs' competitiveness but does not moderate the relationship between authenticity and human capital. These findings suggest that to enhance the brand image and authenticity of cultural products, MSMES must possess adaptive capabilities that enable them to respond to market changes and maintain the relevance of their products.